Developing adobe animate-based interactive learning media of table manner for university students - Akmal, Nikmat; Putri, Yuzia Eka; Anugerah, Ajeng Inggit (Universitas Malikussaleh, 2022)
Culinary students faced difficulties in implementing proper table manner at hotel due to their lack of knowledge of how actual implementation of table manner should be. The purpose of this study was to develop Adobe Animate-based interactive learning media about table manner. This study employed Research and Development by Thiagarajan (1974). The data were collected through interview and questionnaire (need analysis and feasibility measurement). The subjects were students and lecturers of Culinary Study Program. The data were analyzed by using descriptive analysis. Adobe Animate-based interactive learning media about table manner was needed by students and lecturers according to their needs. The developed media consists of front display (university logo, material topic, and four buttons linked to the next page), materials, videos, and quiz. The feasibility test result of the developed media according to the material experts, media expert and students was respectively 4.45 (very feasible), 4.4 (very feasible), and 4.44 (very high acceptability). The developed media namely Adobe Animate-based interactive learning media about table manner is very feasible to be used as a learning media.